In vivo sucrose stimulation of colour change in citrus fruit epicarps: Interactions between nutritional and hormonal signals - Iglesias, Domingo J.; Tadeo, Francisco R.; Legaz, Francisco; Primo-Millo, Eduardo; Talón, Manuel (2017)
During ripening, citrus fruit-peel undergoes 'colour break', a process characterized by the conversion of chloroplast to chromoplast. The process involves the progressive loss of chlorophylls and the gain of carotenoids, changing peel colour from green to orange. In the present work, the in vivo and in vitro effects of supplemented nutrients (sucrose and nitrogen) and phytohormones (gibberellins \GA\ and ethylene) on colour change in fruit epicarp of Satsuma mandarin (Citrus unshiu (Mak,) Marc,, cv, Okitsu), were studied, The rate of colour break was correlated positively with sucrose content and negatively with nitrogen content. The removal of leaves blocked natural sucrose build-up and nitrogen reduction in the peel. Defoliation also inhibited chlorophyll disappearance and carotenoid accumulation, thereby preventing colour break. In vivo sucrose supplementation promoted sucrose accumulation and advanced colour break. In both in vivo and in vitro experiments, colour change promoted by sucrose was unaffected by ethylene but delayed by GA,. in non-supplemented plants, ethylene accelerated colour break while GA, had no detectable effects. Ethylene inhibitors effectively counteracted the sucrose effects on colour change. Collectively, these results suggest that the chloroplast to chromoplast conversion in citrus fruit epicarps is stimulated by sucrose accumulation, The sugar regulation appears to operate via ethylene, whereas GA may act as a repressor of the sucrose-ethylene stimulation.